Effect of Respiratory Training combined with Core Stability Training for Children with Spastic Cerebral Palsy - Binong HU; Kai ZHANG; Fang QI; Chunhua WANG; Wenyin ZHOU; Kun AI; Hong ZHANG (康复学报)
Objective:To observe the effect of respiratory training combined with core stability training on motor function, balance function and daily life ability of children with spastic cerebral palsy.Methods:A total of 74 children with spastic cerebral palsy who were treated in the deparment of child rehabilitation of Xiangya fraternity rehabilitation hospital from March to December 2019, which were divided into the control group and the observation group according to the random number table, with 37 cases in each group.In the course of treatment, two cases dropped in each group, and finally 35 cases were included in each group.The control group was given core stability training on the basis of routine rehabilitation training.The routine rehabilitation training mainly included stretching training, joint range of motion training and occupational therapy, 10 minutes each time.Core stability training mainly included bypass training, sitting up training, suspension system training and Bobath ball training, 40 minutes per time.On the basis of routine rehabilitation training in the control group, the core stability training time of the observation group reduced from 40 minutes to 20 minutes each time, and then received respiratory training, 20 minutes each time.Respiratory training mainly includes abdominal respiratory training(7 min per time), chest expanding exercise training(3 min per time), respiratory aid method training(4 min per time), and anti blocking respiratory training(6 min per time).All the above items were trained twice a day, five times a week, continuous treatment for three months.Before and after treatment for three months, D and E functional domains of gross motor function measure scale-88(GMFM-88)was used to assess the gross motor function such as standing, walking, running and jumping; the Berg balance scale(BBS)was used to assess the balance function;and the Barthel index(BI)was used to assess the daily life activity ability.Results:Before treatment, there were no significant difference in the D and E functional domains scores of GMFM-88, BBS scores and BI scores between the two groups, with no statistically significant differences(P>0.05).Compared with before treatment, the D and E functional domains of scores GMFM-88, BBS scores, BI scores of the both groups after treatment for three months were significantly improved, with statistically significant differences(P<0.05).Compared with the control group, the D and E functional domains of scoresGMFM-88, BBS scores, BI scores in the observation group were significantly higher than those of the control group, with statistically significant differences(P<0.05).Conclusion:Respiratory training combined with core stability training can significantly improve the gross motor function, balance function and daily life ability of children with spastic cerebral palsy, which is worthy of clinical promotion.